Elaboración de un plan de promoción turístico del cantón Mocache, provincia de Los Ríos. - Núñez Cruz, Yuri Jasmin (2015)
This project aims to develop a plan to promote the tourist attractions of Canton Mocache province of Los Rios. In this research to determine the market survey simple random sampling, with Nel Quezada formula was used giving a total of 377 people to be interviewed, surveys were conducted in urban and rural areas of the county. The SWOT analysis was performed to determine each of the points that can be exploited and the things that you want to improve in the next project. In the promotion and dissemination of attractive advertising it was through brochures, leaflets, TV spots, spots and advertising on radio and newspapers of the town. With the development of this project is intended that the canton Mocache have the opportunity to promote and boost tourism and also to integrate everyone in the industry with regard to restoration, bars accommodations and services. This way you can position the Canton as one of the best rural tourism destinations in the region.